Analisis Realisasi Anggaran Pendapatan dan Belanja Negara (APBN) Pada Institut Agama Islam Negeri Bone - Habibi Habibi (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2021)
Income is the cash inflow obtained from services and asset utilization while expenditure is the expense allocated for running the wheels of the organization which is carried out fairly and evenly so that it can be relatively enjoyed by the community, especially in providing educational services. The purpose of this study was to analyze the realization of the State Revenue and Expenditure Budget at the Bone State Islamic Institute. The data used is the report on the realization of the State Revenue and Expenditure Budget for 2018-2020. The results of this study were to determine the development of income, effectiveness and the level of spending efficiency at the State Islamic Institute of Bone.